COVID-19 survey among people who use drugs in three cities in Norway. (1st December 2020) - Welle-Strand, Gabrielle K.; Skurtveit, Svetlana; Clausen, Thomas; Sundal, Christine; Gjersing, Linn
Highlights: 2/3 of the PWUDs were familiar with COVID-19 related symptoms. 9 out of 10 would take a COVID-19 test if they experienced any symptoms. 2/3 of the sample was not aware of available COVID-19 services. OMT patients were more likely to be familiar with COVID-19 symptoms and services. 2/3 of the participants reported that drugs had become more expensive. Abstract: Background: Little is known regarding what people who use drugs (PWUD) know about COVID-19 related issues and changes in the drug market due to COVID-19. We therefore conducted a survey to explore these issues. Methods: In a cross-sectional study, we interviewed 226 PWUD from three Norwegian cities in May/June 2020. Participants completed an interview-administrated questionnaire. Three separate multiple binary logistic regression models were estimated with the outcomes (no/yes): 1. Familiarity with COVID-19 symptoms, 2. Awareness of COVID-19 services tailored towards PWUD and, 3. Willingness to take a COVID-19 test. Results: The mean age was 44.1 years and 73 % were males. Fifty-four percent were injectors, and heroin/other opioids (35.8 %) and cocaine/amphetamine (25.2 %) were the most common main drugs used. Overall, 54.9 % were in opioid maintenance treatment (OMT). The majority (65.9 %) stated they knew the COVID-19 symptoms. Almost all the participants (91.2 %) reported they would take a COVID-19 test if experiencing relevant symptoms. The majority (63.7 %) were not aware of COVID-19 services available to PWUD. OMT patients were more likely to be familiar with COVID-19 symptoms (aOR = 3.4, 95 % CI 1.7; 6.8), and to be aware of COVID-19 services (aOR = 2.7, 95 % CI 1.1; 6.3). Overall, 35.4 % reported reduced drug availability, mainly for tranquilizers, while 61.5 % reported increased drug prices, mainly for cannabis. Conclusion: Drug treatment may play an important role in COVID-19 prevention, as those in OMT were more likely to be aware of symptoms and of availability of services.